The Dangers of Co-witness Familiarity: Investigating the Effects of Co-witness Relationships on Blame Conformity - Mojtahedi, Dara; Ioannou, Maria; Hammond, Laura (Journal of police and criminal psychology, 2018)
The purpose of this study was to examine the effects of pre-existing relationships between co-witnesses on statement similarity, after a post-event discussion. Although research studies have attempted to observe the effect of a pre-existing relationship on eyewitness pairs, few have investigated these effects on larger groups of co-witnesses. Four hundred and twenty participants took part in an eyewitness simulation experiment. Participants were placed into groups of five, and viewed video footage of a bar fight. After witnessing the event, participants discussed the event with group members before giving individual statements privately. The study employed a one-way between subjects design with three conditions: (1) participants discussed the event with familiar co-witnesses, (2) participants discussed the event with unfamiliar co-witnesses and (3) participants were not permitted to discuss the event with their co-witnesses (control). It was found that post-event discussion between co-witnesses increased the level of similarity in blame attribution within the eyewitness groups; however, this difference was only significant in groups where eyewitnesses shared a pre-existing relationship. In addition, the level of uncertainty was reduced when eyewitnesses took part in post-event discussions. It is suggested that this might be attributed to an increased level of informational influence between familiar co-witnesses. However, there was no evidence suggesting that post-event discussions led to an increase in false eyewitness statements.